Hans-Georg Gadamer – doświadczanie granicy języka - Garncarek, Piotr (Postscriptum Polonistyczne, 2020)
The article discusses the usefulness and adequacy of hermeneutic theory of language by HansGeorg Gadamer in glottodidactic process. It presents the attempt to define the phenomenon of language (in this case regarded as a foreign language) that is different than the linguistic one. It is a contribution to further search for different ways of defining a native language while teaching it at Polish faculties abroad. The aim of such search is to find an answer to the question: what is it that we teach?